Age Impact on the Use of Politeness Strategies in Online Interaction by EFL Students in Al-Anbar Distinguished School for Girls - Hamood, Baydaa; Challob, Ala’a (Al-Adab Journal, 2023)
The present paper concentrates on the linguistic behaviors prevailing in EFL students in Al-Anbar distinguished school for Girls. These behaviors are displayed through the choice of language, and politeness strategies employed by EFL students in their interaction with each other. Thus, the population of the current study is EFL students from the second intermediate and fifth preparatory classes in the secondary distinguished school for girls in Al-Anbar Province in the first and second semester of their academic year 2021-2022. Based on this population, a total of 40 students have volunteered to participate in this study. The age of the participants is in-between (14-17) years. Consequently, more than 30 samples of their online messages are collected by the researcher. These messages are sent by the participants of the study via Whatsapp groups established by the teachers of English language in this secondary distinguished school. To deeply explore the politeness strategies and to find the difference in age for these groups, these messages are analyzed by adopting the qualitative content analysis technique informed by Brown’s and Levisohn’s theory (1987) of politeness strategies. The findings reveal that EFL students from that school utilize various politeness strategies. Based on the frequency of these strategies, the researcher concludes that the age differences among participants play a pivotal role in determining the application and the choices of politeness strategies through their online interaction. As a result, the data of the present paper shows that participants from fifth stage are more aware and knowledgeable to these strategies than those who are from second intermediate stage.